PENGARUH PENETAPAN DAERAH TUJUAN WISATA AGRO KEBUN SALAK TERHADAP ALIH FUNGSI LAHAN DI DESA SIBETAN, KARANGASEM, BALI - Made Risky Prema Bumi; Wayan Damar Windu Kurniawan (UNHI PRESS, 2021)
This study intends to discuss the effect of determining the destination of salak agro-tourism on land conversion in Sibetan Village. Land conversion is a natural resource that has a very broad function in meeting various human needs. From an economic perspective, land is the main permanent input for various agricultural and non-agricultural commodity production activities. Sibetan Village is one of the areas that has the largest salak plantation on the island of Bali. This village is designated as a tourist destination area, of course, it has an impact on infrastructure development and the conversion of land functions that must be carried out to support the needs that are a requirement as an agro-tourism-based tourism village. The method used in this research is qualitative method and descriptive method. This study uses qualitative and quantitative data which will be analyzed using evaluative analysis. The results showed that the tourism potential in Sibetan Village was abian salak agro-tourism, measurement of natural scenery, arts and culture, salak processing industry and homestays. The conversion of land functions carried out by people who have converted salak plantation lands are salak farmers, tourist attractions entrepreneurs, tourism accommodation actors, traders and carving craftsmen. Factors that affect land conversion are economic factors, social factors, population growth factors and the increasing need for residential land, and agricultural penetration factors. The impact of determining tourist destinations on land conversion activities is that salak plantations are decreasing, the profession of farmers is reduced, infrastructure development is equitable, and the economic turnover of creative industries is increased, such as salak wine, salak coffee, salak bark tea, and salak sweets and chips